2022
DOI: 10.7759/cureus.26068
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Benign Paroxysmal Positional Vertigo and Vitamin D

Abstract: Introduction Benign paroxysmal positional vertigo (BPPV) is a type of vertigo and its signs are short-time, severe attacks that occur in certain head and body positions. Recent studies have revealed that vitamin D deficiency correlates with BPPV and this is explained by cupulolithiasis and canalithiasis theories. Method In the present study, levels of serum vitamin D in the patients who were diagnosed as BPPV and those in the control group consisting of healthy individuals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Seven articles investigated serum vitamin D levels in both BPPV cases and controls. Among them, two articles reported a statistically significant difference, indicating that the mean serum vitamin D levels in the BPPV group were notably lower than those in the control group [ 24 , 27 ]. The reported serum vitamin D levels for BPPV cases and controls ranged from 17.1 to 31.4 ng/mL and 17.6 to 30.7 ng/mL, respectively, across the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven articles investigated serum vitamin D levels in both BPPV cases and controls. Among them, two articles reported a statistically significant difference, indicating that the mean serum vitamin D levels in the BPPV group were notably lower than those in the control group [ 24 , 27 ]. The reported serum vitamin D levels for BPPV cases and controls ranged from 17.1 to 31.4 ng/mL and 17.6 to 30.7 ng/mL, respectively, across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…In line with these findings, another investigation indicated that individuals with recurrent BPPV exhibited notably diminished levels of vitamin D upon initial diagnosis, in contrast to those without recurrences (29.0 ± 12.0 vs. 37.6 ± 18.3 ng/mL; p = 0.012) [ 25 ]. Additionally, Resuli et al reported that individuals in the BPPV group had significantly lower vitamin D levels than those in the control group [ 24 ]. Bazoni et al, on the other hand, found no association between 25(OH) vitamin D levels and BPPV in the general population, but noted an association with bone mineral density in the elderly group with diabetes mellitus and BPPV [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…By allowing extra time for the treatment session, clinics provide sufficient time for patients to recover following repositioning manoeuvres. The session can also be used to identify risk factors for recurrence that may not have been previously discussed, such as vitamin D deficiency and poorly controlled type II diabetes, 19 both identified to be represented in higher numbers in those with BPPV. A recent systematic review and meta-analysis 20 supports the recommendation that all fallers should be screened and, if found to have BPPV, treated with effective manoeuvres.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systematic review revealed that age is not considered a risk factor for the recurrence of BPPV [10]. While, a recent study from Iraq reported that the age might be a risk factor for BPPV recurrence [28].…”
Section: • Causesmentioning
confidence: 99%